Collaboration and Technology : 21st International Conference, CRIWG 2015, Yerevan, Armenia, September 22-25, 2015, Proceedings /: 21st International Conference, CRIWG 2015, Yerevan, Armenia, September 22-25, 2015, Proceedings. (2015) - Unknown
No abstract available